Strategi Pengembangan Bisnis Ikan Pora-Pora (Studi Pada CV. Crispy Pora-Pora Percut Sei Tuan Deli Serdang) - Jefri J Sianturi (Jurnal Niaga & Bisnis (e-journal), 2015)
This study was conducted to search for internal and external factors, namely the company's strengths, weaknesses, opportunities and threats in formulating strategies that will be used in the development of its business. The method used in this research is descriptive qualitative approach. Data collection techniques do interviews   and give questionnaires to the leading companies. The determination of the strategy, using internal and external factors    in the form of a SWOT analysis. After the SWOT analysis of the obtained values ​​IFAS and EFAS company that will be used in the internal matrix external (IE). The results of the study, selection strategies that can be used by the company is the intensive strategy , to conduct   market penetration, market development and product development. Keywords: strategy, business development, SWOT analysis